Ethical, legal, and social aspects of health technologies for home-based paediatric palliative care – a systematic review - Erik Bjørnerud; Simen A. Steindal; Bjørn M. Hofmann; Anette Winger; Kirsti Riiser; Weiqin Chen; Heidi Holmen (BMC Palliative Care)
Abstract Background Home-based health technologies for paediatric palliative care have great potential to improve care for children, caregivers, healthcare professionals, and health systems. However, no systematic reviews have directly addressed the intersections among the ethical, legal, and social aspects of these technologies for paediatric palliative care. The objective of this systematic review was to identify and analyse the ethical, legal, and social aspects of health technologies for home-based paediatric palliative care. Methods We have conducted a systematic review, inspired by the framework suggested by McCullough. We registered the review protocol in PROSPERO (CRD42024496034) and conducted a systematic search in six databases (ASSIA, Cinahl, Embase, Medline, PsycInfo, and Web of Science) on 27 November 2023 to identify relevant studies. Pairs of authors independently assessed the eligibility of the studies and extracted data. The eligible studies employed a range of different methods from randomised controlled trials to usability studies. We then synthesised the data according to the ethical, legal and social aspects of the technologies. Results Overall, our search resulted in 9,545 reports, which were screened after deduplication. The quality of the reports was assessed according to being published in peer reviewed journals. Fifteen reports were included, which showed that the main ethical issues are harm reduction, improved services, agency and autonomy, trust and empowerment. The main legal aspects are privacy equal access to care, participation in decisions and standardisation. The main social issues are cost reduction, transformation of family relations and novel modes of communication. Health technologies have the potential to alleviate burdens and improve the quality of care for children in paediatric palliative care and their families, but they also create novel burdens through constant reporting requirements and the vulnerability of some health technologies to technological malfunction. Nevertheless, they can increase family inclusion and children’s autonomy and participation, thus empowering children, particularly through co-development of solutions. Furthermore, studies have indicated that health technologies themselves may have positive effects on children’s health. The legal aspects of health technologies pertain to privacy and control over one’s health information and equitable access to care and participation in care, while social issues can potentially reduce costs for health systems but also involve novel costs. Conclusion The reviewed studies concerning the co-development of health technologies reported increased benefits in terms of health, agency, well-being, and strengthened children’s rights in home-based paediatric palliative care. However, the social dimensions of such technologies can lead to both public savings and reconfiguration of family constellations. We recommend that future researchers consider privacy, the formal dimensions of apps and smartphones, and their impacts on families. PROSPERO reference CRD42024496034.